Volume 8C: Heat Transfer and Thermal Engineering 2013
DOI: 10.1115/imece2013-62620
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mixed Hydrophilic and Hydrophobic Surfaces on Frost Nucleation and Growth

Abstract: The purpose of this research is to test hydrophilic, hydrophobic, and mixed hydrophobic and hydrophilic (biphilic) surfaces to see how theses surfaces affect frost nucleation and growth. Frost forms when humid air comes into contact with a surface that is below the dew point and freezing temperature of water. Many engineering systems are hindered by frost, such as aeronautics, refrigeration, and electrical transmission wires. Most recent research on frost formation has looked at making superhydrophobic materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Combination of both hydrophilic and hydrophobic properties in one material can lead to the synergism of properties and effects. This idea can be realized through surfaces with chemical heterogeneity. For instance, Van Dyke et al showed that chemical heterogeneity, created on surfaces by photolithography in combination with the modification of a hydrophobic substrate with hydrophilic octadecayltrichlorosilane, allowed for a suppression of the freezing temperature of water, freezing time delay, and control of coalescence dynamics. , Murase et al showed a reduction of ice adhesion and prevention of snow accretion on nanoscale surfaces based on organopolysiloxane modified with lithium …”
Section: Introductionmentioning
confidence: 99%
“…Combination of both hydrophilic and hydrophobic properties in one material can lead to the synergism of properties and effects. This idea can be realized through surfaces with chemical heterogeneity. For instance, Van Dyke et al showed that chemical heterogeneity, created on surfaces by photolithography in combination with the modification of a hydrophobic substrate with hydrophilic octadecayltrichlorosilane, allowed for a suppression of the freezing temperature of water, freezing time delay, and control of coalescence dynamics. , Murase et al showed a reduction of ice adhesion and prevention of snow accretion on nanoscale surfaces based on organopolysiloxane modified with lithium …”
Section: Introductionmentioning
confidence: 99%